The Relationship Between Macronutrient Intake and Body Composition with Physical Fitness in Non-Elite Athletes of the UNESA Badminton Club - Pramesti, Radita; Satwika Arya Pratama, (Jurnal Gizi dan Kesehatan Nusantara, 2025)
Background: Optimal nutrient intake is essential to support athletes' performance, while body composition significantly affects fitness and performance. Purpose: This study aims to determine the relationship between macronutrient intake and body composition on physical fitness in non-elite athletes at the Badminton Student Activity Unit of the State University of Surabaya. Methods: This research is quantitative with a cross-sectional design, involving 37 non-elite athletes as respondents. Nutrient intake was collected using the Semi Quantitative Food Frequency Questionnaire (SQ-FFQ). Body composition was measured using Bioelectrical Impedance Analysis (BIA), and physical fitness was assessed using the Multistage Fitness Test (MFT). Data analysis was conducted using Spearman's Rank correlation test. Results: The results of the study showed that fat intake was significantly related to physical fitness in female respondents (p = 0.001; r = –0.798). Protein intake in women showed a significant relationship with (p = 0.049; r = -0.533). Body fat, visceral fat, subcutaneous fat throughout the body, and skeletal muscle throughout the body p < 0.005 were significantly related to physical fitness. Conclusion: In conclusion, body composition has a more significant relationship with physical fitness compared to macronutrient intake.